Complete mitochondrial genome assembly of Zizania latifolia and comparative genome analysis - Luo, Xianyang; Gu, Cuicui; Gao, Sijia; Li, Man; Zhang, Haixiang; Zhu, Shidong (Frontiers in Plant Science, 2024)
Zizania latifolia (Griseb.) Turcz. ex Stapf has been cultivated as a popular aquatic vegetable in China due to its important nutritional, medicinal, ecological, and economical values. The complete mitochondrial genome (mitogenome) of Z. latifolia has not been previously studied and reported, which has hindered its molecular systematics and understanding of evolutionary processes. Here, we assembled the complete mitogenome of Z. latifolia and performed comprehensive analysis including genome organization, repetitive sequences, RNA editing event, intercellular gene transfer, phylogenetic analysis, and comparative mitogenome analysis. The mitogenome of Z. latifolia was estimated to be a circular molecule of 392,219 bp and 58 genes consisting of three rRNA genes, 20 tRNA genes, and 35 protein-coding genes (PCGs). There were 46 and 20 simple sequence repeats (SSRs) with different motifs identified from the mitogenome and chloroplast genome of Z. latifolia, respectively. Furthermore, 49 homologous fragments were observed to transfer from chloroplast genome to mitogenome of Z. latifolia, accounting for 47,500 bp, presenting 12.1% of the whole mitogenome. In addition, there were 11 gene-containing homologous regions between the mitogenome and chloroplast genome of Z. latifolia. Also, approximately 85% of fragment from mitogenome was duplicated in the Z. latifolia nuclear genome. Selection pressure analysis revealed that most of the mitochondrial genes were highly conserved with the except for ccmFc, ccmFn, matR, rps1, and rps3. 93 RNA-editing sites were found in the PCGs of mitogenome. Z. latifolia and Oryza minua are most closely related, as shown by collinear analysis and the phylogenetic analysis. We found that repeat sequences and foreign sequences in mitogenomes of Oryzae plants were associated with genome rearrangements. In general, the availability of the Z. latifolia mitogenome will contribute valuable information to our understanding of the molecular and genomic aspects of Zizania.